Antibacterial Test of Endophytic Fungi of Red Ginger Rhizome (Zingiber officinale Rosc) Against Bacillus cereus - Kusuma, A. A. Ngurah Nara; Sarkono, Sarkono; Ernin Hidayati; Faturrahman, Faturrahman; Bambang Fajar Suryadi; Made Raningsih (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Busy activities make people prefer to consume ready-to-eat food which sometimes does not guarantee the level of cleanliness, so that cases of food poisoning often occur. Bacillus cereus is a bacteria that causes food poisoning which is usually found in rice. To overcome this problem, research was carried out to find new sources of medicine from endophytic fungi, namely fungi that live in plant tissue. The addition of clinical drugs derived from fungi has attracted interest in the discovery of new secondary metabolites derived from endophytic fungi. This research aims to (1) obtain endophytic fungal isolates isolated from red ginger rhizomes, (2) obtain endophytic fungal isolates that are antibacterial against Bacillus cereus. The method used is a laboratory experiment by randomizing and repeating the samples. The results showed that four isolates of endophytic fungi were successfully isolated from red ginger rhizomes with varying inhibitory abilities between isolates. The highest percentage of inhibitory power based on the in vitro dual culture assay was a cream colored isolate of 100 ± 0.0%.